Quantification and characterization of mesoscale eddies with different automatic identification algorithms - Viikmaee, Bert; Torsvik, Tomas (Journal of coastal research, 2013)
Automatic methods for detection of mesoscale eddies are usually based on either physical or geometrical flow characteristics. In this article, a hybrid method combining the strengths of the two different approaches is applied to the Eulerian velocity fields for two case studies: the Gulf of Finland (the Baltic Sea) and the Raunefjord and Vatlestraumen area south-west of Bergen, Norway. Velocity fields are investigated with a hybrid winding-angle method (HWA), where the Okubo-Weiss parameter is first used to detect potential eddies, and the winding-angle method is used locally within these regions to test the Okubo-Weiss result. In the Gulf of Finland, the HWA method results in a substantially reduced number of detected eddies compared with the Okubo-Weiss result, indicating that the Okubo-Weiss parameter severely overestimates the number of eddies. In Vatlestraumen, there was a better correspondence between results obtained by the HWA and the Okubo-Weiss methods. The HWA method requires careful analysis since more than one streamline may identify the same eddy structure.